The Family as a Domestic Church Becomes the Primary Educator for Children - Paulinus Tibo; Ona Sastri Lumban Tobing (Indonesian Journal of Educational Science and Technology, 2023)
The family is the first and foremost educator in terms of faith and noble values through the relationships that occur both between husband and wife, parents and children, and relationships between children. This study aims to find three concepts of parents as priests, prophets and kings. Researchers conducted qualitative research with the results of observations, interviews and documentation used by researchers to determine the implementation of the family as the household church of the parish of St. Peter and Paul Kabanjahe. The informants used were 15 families consisting of 15 parents and 15 children. The data analysis process uses technical triangulation and source triangulation. Based on the findings of the researchers, the implementation of the family as a household church has not been fully implemented due to a lack of family understanding of the real household church. In this case the family emphasizes physical life rather than spiritual life. The recommendation in this study is that it is necessary to carry out catechesis to build parents' understanding as a household church in children's education.